ผลของการจัดประสบการณ์แบบโครงการที่มีต่อความคิดสร้างสรรค์ของเด็กปฐมวัย (THE EFFECTS OF EXPERIENCIAL PROJECT APPOACH ON CREATIVE THINKING OF KINDERGARTENERS) - จงบุรี ฌานิกา; สาริปา อารี; เต็มรัตน์ สุภาพ (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2011)
การวิจัยในครั้งนี้มีวัตถุประสงค์เพื่อ 1) เปรียบเทียบความคิดสร้างสรรค์ของเด็กปฐมวัยก่อนและหลังได้รับการจัดประสบการณ์แบบโครงการ 2) ศึกษาความคิดสร้างสรรค์ของเด็กปฐมวัยขณะได้รับการจัดประสบการณ์แบบโครงการ และ 3) เปรียบเทียบความคิดสร้างสรรค์ของเด็กปฐมวัยหลังได้รับการจัดประสบการณ์แบบโครงการกับเกณฑ์ร้อยละ 80 ของคะแนนเต็ม กลุ่มตัวอย่างที่ใช้ในการวิจัย คือ เด็กปฐมวัยอายุระหว่าง 5-6 ปี กำลังศึกษาในชั้นอนุบาลปีที่ 2 ภาคเรียนที่ 2 ปีการศึกษา 2551 โรงเรียนบ้านคลองเหลง ตำบลควนทอง อำเภอขนอม จังหวัดนครศรีธรรมราช สังกัดสำนักงานเขตพื้นที่การศึกษานครศรีธรรมราช เขต 4 จำนวน 25 คน ซึ่งได้มาโดยวิธีการสุ่มอย่างง่าย (Simple random sampling) โดยมีโรงเรียนเป็นหน่วยในการสุ่ม การวิจัยนี้ใช้ระเบียบวิธีวิจัยเชิงกึ่งทดลอง แบบมีการทดสอบก่อนและหลังกับกลุ่มเดียว (One group pretest-posttest design) เครื่องมือที่ใช้ในการวิจัย ได้แก่ แผนการจัดประสบการณ์แบบโครงการ จำนวน 2 โครงการ ใช้สอน 20 ครั้ง รวม 28 ชั่วโมง และแบบทดสอบวัดความคิดสร้างสรรค์จากการวาดภาพของเจลเลนและเออร์บัน สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน การทดสอบค่าที และการวิเคราะห์เนื้อหา ผลการวิจัยพบว่า 1. เด็กปฐมวัยที่ได้รับการจัดประสบการณ์แบบโครงการ มีความคิดสร้างสรรค์หลังเรียนสูงกว่าก่อนเรียน อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.01 2. ความคิดสร้างสรรค์ของเด็กปฐมวัยขณะได้รับการจัดประสบการณ์แบบโครงการมีความคิดคล่องแคล่วมากที่สุด รองลงมา คือ ความคิดริเริ่ม ด้านความคิดละเอียดลออ ด้านการสร้างเรื่องราว ด้านความคิดยืดหยุ่น ด้านการกระทำที่เสี่ยงและด้านอารมณ์ขันน้อยที่สุด 3. ความคิดสร้างสรรค์ของเด็กปฐมวัยที่ได้รับการจัดประสบการณ์แบบโครงการ สูงกว่าเกณฑ์ที่กำหนด อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.01 โดยได้คะแนนคิดเป็นร้อยละ 80.78 คำสำคัญ: เด็กปฐมวัย การจัดประสบการณ์แบบโครงการ ความคิดสร้างสรรค์ The purposes of this research were: 1) to compare creative thinking of kindergarten students before and after learning through experiencial project approach, 2) to find out creative thinking of kindergarten students that occured during experiencial project approach lessons, and 3) to compare creative thinking of kindergarten students after learning through experiencial project approach with the criteria 80% of the total score. The research samples were derived from simple random samping technique. The school was taken as a unit of sampling. There were twenty-five children aged from five to six years old, studying in the second year of kindergarten level in the second semester of 2008 academic year in Bankhongleng School, Thambon Kuanthong, Amphoe Khanom, Nakhon Si Thammarat Province under Nakhon Si thammarat Educational Service Area Office 4. The study employed a quasi experimental research methodology; a one group pretest and posttest design was applied. The research instruments were 20 lesson plans of two project topics for 28 hours, and the test for creative thinking-drawing production developed by Jellen and Urban. Data were analyzed through arithmetic mean, standard deviation, t-test, and content analyzesia. The results were as follows: 1. The kindergarten students learning through experiencial project approach obtained creative thinking scores in the posttest statistically higher than in the pretest at the 0.01 level of significance. 2. The most aspects of creative thinking that occured during experiencial project approach lessons was fluency followed by originality, elaboration, story flexibility, risk and humor respectively. 3. The kindergarten students learning through experiencial project approach obtained creative thinking in the posttest statistically higher than the stated criteria score at the 0.01 level of significance. in that the posttest score was 80.78 Keywords: Kindergartener, Experiencial Project Approach, Creative thinking